IDENTIFYING TEACHER PROFESSIONAL IDENTITY IN THE CONTENT OF PRE-SERVICE TEACHERS’ REFLECTION ON TEACHER’S TEACHING PRACTICUM - Martina Mulyani; Muhammad Handi Gunawan; I Putu Indra Kusuma (University of Kuningan, 2022)
Teaching practicum is believed to be a program crucial for pre-service teachers to gain their teacher professional identity (TPI). The pre-service teachers (PST) who are able to fit the context and be reflective to cope with challenges in the program are believed to have the sense of TPI. Hence, a PST o pre-service teachers is expected to have deeper focus of reflection after experiencing teaching practicum. One of the tools to identify the TPI among PSTs is Onion Model, the model containing the five phases of structured reflection. Even though there are a large number of researches that examine the reflection of teaching practicum through the eyes of PSTs using a number of different tools, few are concerned with the focus of PST’s reflection to determine their TPI. This research employed case study and Onion Model as the tool of analysis, the study scrutinized the TPI among six PSTs who possess different intentions in joining the teacher college. The finding showed that, as a training session, teaching practicum is able to sharpen the TPI among PSTs. However, it cannot change those with multiple identities and fixed personalities who may think that conflicts in identities can lead to diminished well-being.Keywords: pre-service teacher; teacher professional identity; teaching practicum.